Recruitment of Persons in Terrorist Organizations, his Techniques, his Methods - UAE Law as a Model - Al-Khatery, Rashid; Ali, Zayed (Journal of Legal Sciences, 2023)
This study aims to investigate the nature of the recruitment of people into terrorist organizations that have spread in international societies, this phenomenon that did not arise out of a vacuum, but rather that it has its causes and its intellectual, psychological, political, and social motives, as well as economic and educational motives. These reasons may be intertwined with each other, so today we are facing an important and dangerous issue launched by terrorist organizations, by recruiting certain people, who are carefully selected and according to specific specifications, taking advantage of their social and family problems, the class differences they suffer from in their societies, and their desire for revenge, for their feelings Inferiority, contempt, marginalization of their personality and selves, and other reasons that terrorist groups used as a loophole to enter and control them. Hence, the issue of recruiting people into terrorist groups is the main reason behind the spread of terrorism. In order for us to reach the optimal solution to combat it and reduce its danger, it is necessary to identify the psychology of these people, and their psychological and intellectual aspects that made them vulnerable to foreign influences, and to search for the main reasons that prompted them to join these groups